Combustion Performance and Thermal Stability of Basalt Fiber-Reinforced Polypropylene Composites - Tang, Chunhong (Polymers (Basel), 2019)
In this study, the thermal stability and combustion performance of basalt fiber reinforced polypropylene (BFRPP) composite and pure polypropylene (PP) were compared. The results show that the basalt fiber has no positive effect on increasing the initial decomposition temperature of PP, but it could reduce the maximum thermal decomposition rate and increase the temperature of the maximum thermal decomposition rate. Adding basalt fiber to PP could slightly reduce the limiting oxygen index. At the same oxygen concentration, the BFRPP burned significantly more slowly than the PP. In addition, during the combustion, it was observed that the BFRPP showed a better anti-melt dripping effect than the PP. The results from the cone calorimeter test show that, under the same external heat flux, the time-to-ignition (TTI) of BFRPP was less than that of PP. This indicated that BFRPP was easier to ignite than PP. It was also found that the reciprocal of the square root of the TTI of both has a linear relationship with external heat flux. BFRPP has a lower peak heat release rate and total heat release than PP. Moreover, BFRPP produced less smoke than PP when burned.